Bacteria Elimination of Xanthomonas axonopodis pv. glycine and Improvement of Viability of Soybean Seeds Through a Combination of Temperature and Duration of Dry Heat Treatment - Aprilia Diandra Savitri; Imelda Milaros; Irene Patria Hannyvone; Evan Purnama Ramdan (Agrotechnology Research Journal, 2024)
Soybean is the main food crop in Indonesia, besides rice and corn, and its need continues to increase. X. axonopodis pv. glycine (Xag) is a pathogen that causes bacterial pustule disease in soybeans, which can cause soybean productivity to decrease by 57.61%. Xag is also a seed-borne pathogen that spreads through seeds, reaching 8%. Therefore, this study aims to determine the optimum combination of dry heat treatment techniques to eliminate Xag and increase seed viability and vigor. The study was arranged in a randomized complete factorial design consisting of 2 factors: the temperature factor of control, 25 and 45°C, and the duration factor of 6, 12, and 18 hours. Soybean seeds inoculated with Xag were then given a dry heat treatment (DHT) treatment of 100 seeds each. Then, the population of Xag bacteria, germination, vigor index, and seed viability were calculated. The results showed that DHT with a temperature of 45 °C was the best in suppressing the Xag population but reduced soybean seed viability. Therefore, the optimal combination of DHT to eliminate and maintain seed viability is at 25 °C for 12 hours.